2013
DOI: 10.1039/c3cc42732c
|View full text |Cite
|
Sign up to set email alerts
|

The first purification and unequivocal characterization of the radical form of the carbon-centered quinone ketoxy radical adduct

Abstract: We found, unexpectedly, that the radical form of the carboncentered quinone ketoxy radical adduct with a recently developed spin-trapping agent BMPO can not only be directly detected and identified using HPLC/high resolution MS, but can also be isolated and purified using semi-preparative HPLC, enabling direct observation of its clean 6-line ESR signal.Halogenated quinones are a class of toxicological intermediates which can cause acute hepatoxicity, nephrotoxicity, and carcinogenesis. 1,2 They have also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Previous studies have utilized spin trapping in combination with mass spectrometry to confirm the identity of spin trapped radical adducts with both DMPO and BMPO spin traps [5762]. Here, we report for the first time on the detection and identification of a hydroperoxyl-adduct of BMPO when OxDC reacts with oxalate under turnover conditions.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies have utilized spin trapping in combination with mass spectrometry to confirm the identity of spin trapped radical adducts with both DMPO and BMPO spin traps [5762]. Here, we report for the first time on the detection and identification of a hydroperoxyl-adduct of BMPO when OxDC reacts with oxalate under turnover conditions.…”
Section: Introductionmentioning
confidence: 81%
“…During our study of metal-independent hydroxyl/alkoxyl/ketoxy radical production by halogenated quinones and H 2 O 2 (or organic hydroperoxides) 20 21 22 23 24 25 , and their potential biological effects 26 , we found that unprecedented hydroxyl radical-dependent two-step chemiluminescence could be generated by polyhalogenated quinones and H 2 O 2 23 . Recently, we also observed an intrinsic CL generation by all 19 chlorophenols (the parent compounds of chlorinated quinones) and the classic • OH-generating Fenton system, even in the absence of fluorescent agents 27 .…”
mentioning
confidence: 93%
“…The most well-known pathway for • OH generation is through the classic Fenton or Fenton-like reactions mediated by reactive transition metal ions [37,38]. We recently found an unprecedented metal-independent • OH-generating system: polyhaloquinones and H 2 O 2 , and the molecular mechanism of typical nucleophilic substitution coupling with homolytic decomposition for • OH generation was proposed [3,[39][40][41][42][43][44][45][46][47]. More interestingly, an unexpected intrinsic CL emission can also be produced in this novel • OH-generating system, which was found to be specifically dependent on • OH production [44,[48][49][50][51].…”
Section: Unprecedented • Oh Generation and CL Emission Can Be Produced From H 2 O 2 And Polyhaloquinones The Carcinogenic Metabolites Of mentioning
confidence: 99%